The Role of Working Memory in Dual-Target Visual Search - Gorbunova, Elena S.; Kozlov, Kirill S.; Le, Sofia Tkhan Tin; Makarov, Ivan M. (Frontiers in Psychology, 2019)
Visual search for multiple targets is especially error prone. One of these errors is called subsequent search misses (SSM) and represents a decrease in accuracy at detecting a second target after a first target has been found. One of the possible explanations of SSM errors is working memory (WM) resource depletion. Three experiments investigated the role of WM in SSM errors using a dual task paradigm. The first experiment investigated the role of object WM using a classical color change detection task. In the second and the third experiments, a modified change detection task was applied, using shape as the relevant feature. The results of our study revealed no effect of additional WM task on second target detection in dual-target visual search. At this end, SSM errors are not related to working memory resource depletion. On the contrary, WM task performance was violated by dual-target visual search as compared to single-target visual search, when the targets in visual search task were defined by the same feature used in WM task.